Mitochondria-endoplasmic reticulum contacts in sepsis-induced myocardial dysfunction - Jiang, Tao; Wang, Qian; Lv, Jiagao; Lin, Li (Frontiers in Cell and Developmental Biology, 2022)
Mitochondrial and endoplasmic reticulum (ER) are important intracellular organelles. The sites that mitochondrial and ER are closely related in structure and function are called Mitochondria-ER contacts (MERCs). MERCs are involved in a variety of biological processes, including calcium signaling, lipid synthesis and transport, autophagy, mitochondrial dynamics, ER stress, and inflammation. Sepsis-induced myocardial dysfunction (SIMD) is a vital organ damage caused by sepsis, which is closely associated with mitochondrial and ER dysfunction. Growing evidence strongly supports the role of MERCs in the pathogenesis of SIMD. In this review, we summarize the biological functions of MERCs and the roles of MERCs proteins in SIMD.